2015
DOI: 10.1038/srep08101
|View full text |Cite
|
Sign up to set email alerts
|

Benefits of rice seed priming are offset permanently by prolonged storage and the storage conditions

Abstract: Seed priming is a commercially successful practice, but reduced longevity of primed seeds during storage may limit its application. We established a series of experiments on rice to test: (1) whether prolonged storage of primed and non-primed rice seeds for 210 days at 25°C or −4°C would alter their viability, (2) how long primed rice seed would potentially remain viable at 25°C storage, and (3) whether or not post-storage treatments (re-priming or heating) would reinstate the viability of stored primed seeds.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
91
0
4

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 149 publications
(110 citation statements)
references
References 25 publications
2
91
0
4
Order By: Relevance
“…4,7) and faster rate of starch breakdown in germinating primed seeds, which presumably provided the substrates necessary for generating the energy required for growth and maintenance processes (Hussain et al 2015b). Conclusively, studies conducted under controlled and field conditions revealed that seed priming can alleviate the negative effects of drought stress on emergence as well as seedling establishment and growth of dry-direct seeded rice.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…4,7) and faster rate of starch breakdown in germinating primed seeds, which presumably provided the substrates necessary for generating the energy required for growth and maintenance processes (Hussain et al 2015b). Conclusively, studies conducted under controlled and field conditions revealed that seed priming can alleviate the negative effects of drought stress on emergence as well as seedling establishment and growth of dry-direct seeded rice.…”
Section: Discussionmentioning
confidence: 96%
“…In rice, amylase activity is highly induced during germination (Hussain et al 2015b); however, this activity begins to appear even earlier, during seed maturation. Present study highlighted the importance of a-amylase activity and total soluble sugar contents during germination and early seedling growth under drought conditions.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Neto et al also supported higher activities of antioxidants in salt tolerant species. A positive correlation of activities of antioxidant enzymes with stress tolerance has been documented , and their enhanced expression has been suggested as a stress marker. The decline observed in the activities of some antioxidants for several salt‐sensitive wheat cultivars at upper limits of salinity might be due to their inability to cope with stress induced oxidative damage.…”
Section: Discussionmentioning
confidence: 97%
“…The high α-amylase activity in primed seeds and seedlings is also reflected through higher soluble sugar concentrations and a faster rate of starch breakdown in germinating primed seeds, which presumably provided the substrates necessary to generate the energy required for growth and maintenance processes. It has also been proposed that the degradation and conversion of seed reserves during the germination process are related to the increase in soluble sugar contents, which presumably provides the substrates necessary to generate the energy required for growth and maintenance processes (Hussain et al 2015). In addition to the mechanisms associated with starch metabolisms, the chilling tolerance during rice seed germination and early seedling growth induced by seed treatments might be attributed to increased level of antioxidant activity and greater membrane stability (Pouramir et al 2014; Khaliq et al 2015).…”
Section: Discussionmentioning
confidence: 99%